Implementasi Perlakuan Akuntansi Aset Biologis Berbasis PSAK 69 yang Berlaku Efektif 1 Januari 2018 Pada Perusahaan Perkebunan (Studi Kasus PT.PP London Sumatera Indonesia,Tbk) - Rachmawati, Yuni; Oktariyani, Amanda; Ermina (Akuntansi dan Manajemen, 2019)
Biological Assets in plantation industry has increasing in value through biological transformation. This different characteristic allow the information to be presented more biased than others industries. PSAK 69- Agricultur authorized by Dewan Standar Akuntansi Keuangan (DSAK) and effective per 1 Januari 2018,require all plantation industries to use the standard for the December 31 financial statements. PT PP London Sumatera Indonesia,Tbk as a leading and rapidly growing company was a strong reason for the selection of this research object. The purpose of this research was to analyze how to adopt biological assets based on PSAK 69. This research used library studies and field research and analyze using descriptive qualitative. The result show that PT PP London Sumatera Indonesia,Tbk have made recognition, measurement and reporting based on PSAK 69 except in biological assets depreciation.